2016
DOI: 10.3348/kjr.2016.17.5.771
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Performance of FlightPlan during Chemoembolization for Hepatocellular Carcinoma: Importance of the Proportion of Segmented Tumor Area

Abstract: ObjectiveTo evaluate retrospectively the clinical effectiveness of FlightPlan for Liver (FPFL), an automated tumor-feeding artery detection software in cone-beam CT angiography (CBCTA), in identifying tumor-feeding arteries for the treatment of hepatocellular carcinoma (HCC) using three different segmentation sensitivities.Materials and MethodsThe study included 50 patients with 80 HCC nodules who received transarterial chemoembolization. Standard digital subtracted angiography (DSA) and CBCTA were systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A total of 12 studies were reported on feeder detection software 11–22 . This visualisation and guidance software utilises a CBCT dataset to distinguish and define all vessels from the imaging source to the tumour via contrast‐enhanced arteries, with the goal to avoid non‐target embolisation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 12 studies were reported on feeder detection software 11–22 . This visualisation and guidance software utilises a CBCT dataset to distinguish and define all vessels from the imaging source to the tumour via contrast‐enhanced arteries, with the goal to avoid non‐target embolisation.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 studies were reported on feeder detection software. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 This visualisation and guidance software utilises a CBCT dataset to distinguish and define all vessels from the imaging source to the tumour via contrast‐enhanced arteries, with the goal to avoid non‐target embolisation. When compared to conventional DSA the software demonstrated a significant improvement in accurately detecting feeding arteries by 43%.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the DTA studies, one reviewer experienced in DTA studies selected eligible articles according to criteria established elsewhere ( 9 ) with additional confirmation by another DTA expert in cases of ambiguity. Of the initial 124 candidate articles, 63 articles ( 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 ) were finally included. Regarding the studies that analyzed reliability, eligible articles were chosen by consensus after review by two of four independent reviewers experienced in the relevant methodology.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, this technique has been supplemented with a three-dimensional (3 D) cone beam CT (CBCT) that includes opacification of vessels by making the detection of segmental and subsegmental arteries supplying the target tumor easier [ 44 ]. In addition, several studies have been evaluating with favourable results, the role of automatic feeder detection (AFD) software in the analyzation and digital process of CBCT imaging for simplifying and shortening the procedures of hepatic arterial port-a-cath system implantation [ 44 , 45 , 46 , 47 , 48 ]. Possible causes of failure of port-a-cath placement must be considered in this preliminary phase to evaluate if the patient is a suitable candidate for HAI.…”
Section: Hepatic Arterial Infusion Technical Proceduresmentioning
confidence: 99%